2018
DOI: 10.1111/ejn.14185
|View full text |Cite
|
Sign up to set email alerts
|

Circadian regulation in the retina: From molecules to network

Abstract: The mammalian retina is the most unique tissue among those that display robust circadian/diurnal oscillations. The retina is not only a light sensing tissue that relays light information to the brain, it has its own circadian “system” independent from any influence from other circadian oscillators. While all retinal cells and retinal pigment epithelium (RPE) possess circadian oscillators, these oscillators integrate by means of neural synapses, electrical coupling (gap junctions), and released neurochemicals (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 305 publications
(464 reference statements)
3
41
0
Order By: Relevance
“…Research supporting circadian regulation in these regions is described below in sections ordered by the five primary brain divisions. It is also important to note that an overview of the retina is not included below because the importance of the retinal circadian clock is covered elsewhere in this Special Issue (Ko, ).…”
Section: Suprachiasmatic Nucleus Of the Hypothalamusmentioning
confidence: 99%
“…Research supporting circadian regulation in these regions is described below in sections ordered by the five primary brain divisions. It is also important to note that an overview of the retina is not included below because the importance of the retinal circadian clock is covered elsewhere in this Special Issue (Ko, ).…”
Section: Suprachiasmatic Nucleus Of the Hypothalamusmentioning
confidence: 99%
“…The retina is a part of the central nervous system (CNS) and perceived as a "window to the brain" [4] in establishing similarities in the physiology and function of the CNS [5]. The retina also contains a circadian rhythm, and several studies have identified that many aspects of retinal physiology and functions are under the control of a retinal circadian system [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The release of the two primary neurotransmitters, dopamine (DA) and melatonin (MLT), provide the "day" and "night" signals in the retina, which reconfigure retinal circuits and shape the functioning of the retina according to the time of the day [6,9]. Dysfunction of the circadian rhythm within the retina affects adversely the retinal function in the processing of the light information, synaptic communication, and metabolism [8].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the various cells of the retina and the retinal pigment epithelium themselves each bear circadian oscillators that communicate via synapses, gap junctions and released neurochemicals that can diffuse in the extracellular space outside of synapses. The consensus in the literature on the ways in which circadian signals are integrated in this highly organized retinal tissue is summarized in the paper by Ko ().…”
Section: Extra‐scn Oscillatorsmentioning
confidence: 99%